The Implementation of Differentiated Learning to Enhance High School Students’ Learning Independence - Yesita Komalasari (Jurnal Wawasan Nusantara, Scope Pendidikan, 2025)
This study explores the implementation of differentiated learning as an instructional approach to enhance high school students’ learning independence. Differentiated learning emphasizes the adaptation of teaching methods, materials, and assessments to accommodate students’ diverse abilities, interests, and learning styles. The research highlights how this approach fosters student autonomy, motivation, and responsibility in the learning process. Through differentiated strategies such as flexible grouping, tiered assignments, and varied instructional media students are encouraged to take ownership of their learning, set personal goals, and engage in self-directed study. The findings indicate that differentiated learning not only improves academic performance but also nurtures students’ confidence and critical thinking skills. Teachers play a crucial role as facilitators who design learning environments that promote active participation and individual growth. By aligning instructional practices with students’ unique needs, differentiated learning creates equitable opportunities and supports the development of lifelong learning competencies. This approach proves effective in preparing students to face the challenges of higher education and the rapidly changing demands of the modern world.